(untitled) (Itinera, 2025)
Aesthetics of the critical zone: ecology, science, politics Starting from the concept of biodiversity, this contribution explores the intersection between aesthetics and environmental sciences, proposing a methodologically ecological co-implication. Bruno Latour’s thought – reinterpreted here through an aesthetic-ecological lens – plays a key role in deconstructing the modern ontological dualism underlying both certain strands of environmental aesthetics and the very notion of biodiversity. This opens the way for a relational and atmospheric aesthetics attentive to the co-presence of human and non-human actors, and enriched by a culturally situated science. This approach finds concrete expression in the concept of the Critical Zone, understood as a compositional paradigm where beauty emerges as an unstable balance of aesthetic, cognitive, and political elements.